ANÁLISIS DEL IMPACTO DE LA PROFUNDIZACIÓN FINANCIERA EN EL CRECIMIENTO ECONÓMICO DE LA PROVINCIA DE LOJA, PERÍODO 2001-2013. - Elizalde Cabrera, Jonathan Oscar (2015)
The input that financial system gives to Loja province is always a controversial theme because there is not enough information refer to the benefits that financial market give to the economy growing. Theories about economic growing such as Solow (1956) shows that savings and investments generate more capital and then more production on the economy; so that, this theory needs to be proven on the province reality. Facing this problem, this investigation has the purpose to determinate the impact that the financial system has on the economic growing of Loja province in the period 2001-2013. That is why, it refers to savings captured by financial entities and investments that those give to population; related with gross domestic production in this years, through the indicator of financial deepening, which is the quotient between deposits/PIB and credits/PIB. After the analysis, it was determinate that the financial system impact measured by the indicator of financial deepening about savings and credits, is positive in this period; but based on the specific objectives it was determinate that the embracing of the financial entities is located on Loja city which is the capitol of the province of Loja, and in cities on the eastern side of the province; excluding border cantons whom require financial intervention to develop production. Second, the type of credit that financial entities give in the province is the consumer one, but it does not potentiates an economic growing. Finally, the level of financial deepening is better than other provinces from seven region of Ecuador, however in Loja province is evidence a small production development. For this research, it was used information of the financial variables obtained from the Superintendence of Banks and of popular economy; and the data of the gross production of the province is obtained from the Central Bank of Ecuador. It is used the nominal value of the gross domestic production of the province because the information of deposits and credits are only in nominal values. Keywords: Financial deepening, Economic growth, Gross domestic provincial production, catchments, credits.